DESAIN DAN IMPLEMENTASI PENGUKUR KUALITAS UDARA PM10 BERBASIS MIKROKONTROLLER - Nur Arminarahmah; Muhammad Rasyidan; Zaenuddin (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2017)
Air conditions in the environment where the living has begun polluted by pollutants such as land-burning smoke, cigarette smoke, motor vehicle fumes and many other sources of pollutant.We designed a Microcontroller based tool that serves to detect Air quality campus environment of UNISKA Banjarbaru.Sensor used is DSM501a as a sensor measuring levels of pollutants PM10 ,CO2, Smoke. The used is Arduino Uno.